Dynamic simulation and experimental validation of a two-phase closed thermosyphon for geothermal application - Johann-Christoph Ebeling; Xing Luo; Stephan Kabelac; Sebastian Luckmann; Horst Kruse (Propulsion and Power Research, 2017)
The heat transfer performance of a vertical two-phase closed thermosyphon (TPCT) used in a geothermal heat pump was experimentally investigated. The TPCT is a vertical plain steel pipe with inner diameter of 114 mm and bored 368 m deep underground. Carbon dioxide (CO2) is used as working fluid. In the TPCT there is no condensation section. CO2 is condensed by the evaporator of the heat pump, flows into the head of the TPCT and runs down as a falling film along the inner wall of the pipe. For the heat transfer simulation in the TPCT, a quasi-dynamic model in which the mass transfer between the liquid and vapor phases as well as the conduction heat transfer from the surrounding soil towards the pipe is treated dynamically. However the film flow modeling is based on the Nusselt theory of film condensation. The comparison of the experimental data with the numerical simulation is presented and discussed.